2014
DOI: 10.1590/abd1806-4841.20142810
|View full text |Cite
|
Sign up to set email alerts
|

Invasive head and neck cutaneous squamous cell carcinoma: clinical and histopathological characteristics, frequency of local recurrence and metastasis

Abstract: BACKGROUNDsquamous cell carcinoma is the second most common type of skin malignancy and may evolve to regional lymph node and distant metastases. OBJECTIVEThe objective of this study was to evaluate patients with head and neck cutaneous squamous cell carcinoma to identify its clinical and histopathological characteristics, as well as the frequency of local recurrence and metastasis. METHODSA retrospective cohort of patients with head and neck cutaneous squamous cell carcinoma. Inclusion criteria: histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…For the purpose of the present study, PNI was analyzed as a binary variable, including 6 articles, and was associated with an RR of local recurrence (RR [95% CI], 4.30 [2.80–6.60]; P <.01). 8,14,24,33,34,41 A report by Karia et al 6 also indicated that the RR increases with the size of the involved nerve, with RR (95% CI) of regional recurrence for nerves <0.1 mm in diameter of 5.6 (2.0–15.9) ( P =.001) compared with nerves ≥0.1 mm in diameter (RR [95% CI], 10.4 [4.4–24.7]; P <.001). Interestingly, the AJCC Seventh Edition staging system for cSCC 44 includes PNI as a binary variable for high risk, whereas the BWH staging system includes PNI as a risk factor when the involved nerve is ≥0.1 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of the present study, PNI was analyzed as a binary variable, including 6 articles, and was associated with an RR of local recurrence (RR [95% CI], 4.30 [2.80–6.60]; P <.01). 8,14,24,33,34,41 A report by Karia et al 6 also indicated that the RR increases with the size of the involved nerve, with RR (95% CI) of regional recurrence for nerves <0.1 mm in diameter of 5.6 (2.0–15.9) ( P =.001) compared with nerves ≥0.1 mm in diameter (RR [95% CI], 10.4 [4.4–24.7]; P <.001). Interestingly, the AJCC Seventh Edition staging system for cSCC 44 includes PNI as a binary variable for high risk, whereas the BWH staging system includes PNI as a risk factor when the involved nerve is ≥0.1 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor location on the temple, although not part of the AJCC, UICC, or BWH staging system, 44 was associated with a higher risk of recurrence (RR [95% CI], 3.20 [1.1–9.0]; P =.03) than tumor location on either lip or ear, albeit this finding was based on a single, but relatively large, retrospective analysis by Schmults et al 8 Poor differentiation also was found to have statistically significant association with recurrence (RR [95% CI], 2.66 [1.72–4.14]; P <.01), based on pooled data from 11 studies. 4,6,17,19,2224,34,37,39,41 …”
Section: Discussionmentioning
confidence: 99%
“…It is reported that BCC occupies up to 30% of the white people in their lifetimes [Wong et al, 2003], making it the most common cutaneous lesion classification and its incidence has been remarkably increasing 3-10% annually [de Vries et al, 2005;Holterhues et al, 2010;Roewert-Huber et al, 2007]. It is often presented as translucency to fleshy color vessels in BCC and a red, crusted or scaly patch in SCC, and could cause cosmetic influence as well as has a certain degree of metastatic risk, especially the SCC subgroup [Vasconcelos et al, 2014]. In the USA, 180,000-400,000 cases of SCC happened in 2013 [Karia et al, 2013].…”
mentioning
confidence: 99%
“…Systemic ALCL‐ALK− presentation is typically later than for ALK positive disease with a median age of 58 years, is more common in men and has a worse prognosis because of poorer treatment response . ALCL‐ALK− has less than 50% long‐term disease‐free survival rate compared with more than 70% for ALK positive …”
Section: Discussionmentioning
confidence: 99%